Use of nudges to improve food safety in the pork value chain in Viet Nam - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A handbook was distributed to national partners in Viet Nam, including farmer cooperatives and the World Organisation for Animal Health (Tokyo). Anecdotally (no evidence links), the National Institute for Animal Sciences is incorporating nudges in slaughterhouses and traditional markets. Next year translated versions for Cambodia and Laos will be distributed.